Effects of a Nurturing Care Group behavior change program on child protection outcomes in Ghana: A controlled before and after trial. (May 2023) - Forbes, Bill; Fosuah, Cynthia; Tidwell, Ben; Nitkin, Todd; Davis, Tom
Abstract: Background: As part of an effort to rigorously apply behavioral science to child protection efforts, a behavior change model called Nurturing Care Groups (NCGs) was tested for effectiveness in changing child abuse and corporal punishment behaviors. Objective: The primary research question was to what degree NCGs could change child protection knowledge, attitudes, and practices among caregivers in a low-cost program with broad reach, which could feasibly be scaled. Participants and setting: The NCG project was implemented in two distinct ecological zones in Ghana, reaching 73, 959 caregivers of children under 5 across 41 communities; while 20 communities were control sites with no NCG intervention. Methods: Stratified random sampling was used to select intervention area respondents. Cluster sampling was utilized in control areas, using the Probability Proportional to Size method. Standard measures were used to assess changes in practices of violence and abuse, stress experience and management, parenting techniques, and the household environment. Difference-in-difference linear regression was used to compare intervention and control results. Results: Intervention areas demonstrated statistically-significant and substantial changes in reported knowledge, attitudes and behaviors related to physical abuse and corporal punishment. Knowledge of negative impacts of stress on parenting, as well as stress reduction techniques increased in intervention areas, as did positive discipline and parenting practices. Conclusions: The NCG model demonstrated important promising results for changing child protection behaviors in this descriptive study. Statistically-significant decreases in reported physical and psychological punishment and corresponding increases in reported positive discipline indicate that this may be an effective and low-cost intervention for child protection behavior change. Graphical abstract: Unlabelled Image Highlights: Behavioral science provides critical insights to prevention of child abuse. Testing of behavior change approach to corporal punishment and child abuse in Ghana Nurturing Care Groups demonstrate compelling results for changing child protection behaviors.